Active galactic nuclei and their large-scale structure: an eROSITA mock catalogue. Issue 2 (20th May 2019) - Comparat, J; Merloni, A; Salvato, M; Nandra, K; Boller, T; Georgakakis, A; Finoguenov, A; Dwelly, T; Buchner, J; Del Moro, A; Clerc, N; Wang, Y; et al.
Abstract: In the context of the upcoming SRG/eROSITA survey, we present an N -body simulation-based mock catalogue for X-ray-selected active galactic nucleus (AGN) samples. The model reproduces the observed hard X-ray AGN luminosity function (XLF) and the soft X-ray logN–logS from redshift 0 to 6. The XLF is reproduced to within$± 5{{\ \rm per\ cent}}$ and the logN-logS to within$± 20{{\ \rm per\ cent}}$ . We develop a joint X-ray – optical extinction and classification model. We adopt a set of empirical spectral energy distributions to predict observed magnitudes in the UV, optical, and NIR. With the latest eROSITA all sky survey sensitivity model, we create a high-fidelity full-sky mock catalogue of X-ray AGN. It predicts their distributions in right ascension, declination, redshift, and fluxes. Using empirical medium resolution optical spectral templates and an exposure time calculator, we find that 1.1 × 10 6 (4 × 10 5 ) fibre-hours are needed to follow-up spectroscopically from the ground the detected X-ray AGN with an optical magnitude 21 < r < 22.8 (22.8 < r < 25) with a 4-m (8-m) class multiobject spectroscopic facility. We find that future clustering studies will measure the AGN bias to the per cent level at redshift z < 1.2 and should discriminate possible scenarios of galaxy-AGN co-evolution. We predict the accuracy to which the baryon acoustic oscillation standard ruler will be measured using X-ray AGN: better than 3 per cent for AGN between redshift 0.5 to 3 and better than 1 per cent using the Ly α forest of X-ray QSOs discovered between redshift 2 and 3. eROSITA will provide an outstanding set of targets for future galaxy evolution and cosmological studies.